2006
DOI: 10.1016/j.jacc.2006.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Amino-Terminal Pro-Brain Natriuretic Peptide, Galectin-3, and Apelin for the Evaluation of Patients With Acute Heart Failure

Abstract: Our data show potential utility of galectin-3 as a useful marker for evaluation of patients with suspected or proven acute HF, whereas apelin measurement was not useful for these indications. Moreover, the combination of galectin-3 with NT-proBNP was the best predictor for prognosis in subjects with acute HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
351
2
30

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 525 publications
(405 citation statements)
references
References 44 publications
22
351
2
30
Order By: Relevance
“…Recent studies have revealed that Gal-3 appears to be a promising prognostic biomarker in HF patients [3,6,7,21,23,24]. In our study, patients who died during the follow-up period presented significantly higher baseline Gal-3 levels than the survivors, which is in line with some previous reports [3,6,7,21,23,24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recent studies have revealed that Gal-3 appears to be a promising prognostic biomarker in HF patients [3,6,7,21,23,24]. In our study, patients who died during the follow-up period presented significantly higher baseline Gal-3 levels than the survivors, which is in line with some previous reports [3,6,7,21,23,24].…”
Section: Discussionsupporting
confidence: 92%
“…Our preliminary study demonstrated that, among patients with AHF hospitalized in the tertiary care center, the plasma levels of Gal-3 were significantly elevated in comparison with controls without AHF, which is in line with some experimental and clinical studies [3][4][5][6]19].…”
Section: Discussionsupporting
confidence: 89%
“…возрастание уровня галектина-3 коррелировало с возрастом пациентов, ухуд-шением функции почек, тяжестью ХСН. [15] В нашей работе медиана галектина-3 была связана со стадией ХСН ФК NYHA (p<0,05). Уровень галектина-3 в плазме крови больных в группе пациентов с ХСН ФК II NYHA составил 6,85 [3,67; 10,02] нг / мл, в группе пациентов с ХСН ФК III NYHA -9,61 [7,75; 12,6] нг / мл.…”
Section: Discussionunclassified
“…Данные уровни сопоставимы со средней концентрацией этого биомаркера у пациентов с острой СН в других исследованиях [15,16].…”
Section: Discussionunclassified
“…Given NT‐proBNP's strong associations with heart failure, mortality attributable to cardiovascular events, and mortality after cardiac surgery, its inclusion in a prediction model of in‐hospital mortality may serve to improve the model's predictive ability 13, 14, 15, 16. Galectin‐3, a member of the lectin family of proteins, and ST2, a biomarker for cardiac stress, have also been found to be strongly associated with heart failure 17, 18, 19, 20, 21, 22. Additionally, Galectin‐3 has been found to be associated with increased risk for all‐cause mortality in the Framingham Offspring Cohort 23.…”
Section: Introductionmentioning
confidence: 99%